Isolation and Selection of Purple Non-Sulfur Bacteria for Nutrient Rich Biomass Production from Wastes - Minh, Do Binh; Hai, Pham The (VNU Journal of Science: Natural Sciences and Technology, 2021)
Purple nonsulfur bacteria (PNSB) are anoxygenic photosynthetic bacteria, which are able to photoheterotrophically grow in the presence of excessive nutrients. Hence, PNSB can convert organic components, in waste waters into nutrient rich biomass. This suggests the feasibility of converting wastes into valuable products. In this research, method for isolation of PNSB was optimized, and subsequently used for the isolation of  PNSB from domestic waste and pond water samples taken in Hanoi. In addition, the effects of carbon and nitrogen sources and types of waste on biomass and nutrients (protein and carotenes) were also investigated. Four PNSB strains were isolated and based on comparative 16S rDNA analysis and their morphological characteristics, they were identified as Rhodobacter (Rb.) capsulatus, Rhodobacter (Rb.) sphaeroides, Rhodobacter (Rb.) sediminis and Rhodopseudomonas (Rp.) palustris . In terms of the effects of carbon and nitrogen sources on their biomass and nutrient production, glucose or maltose and ammonium chloride or urea were found to be more enhancive than starch and peptone, respectively. Among the studied strains, Rb. capsulatus MD1 and Rb. sphaeroides MD3 showed significantly higher biomass production (up to 0.7 g/l) when growing with various carbon and nitrogen sources, in comparison with the other strains. Moreover,  MD1 and MD3 also produced at least four-fold more carotenoid and up to two-fold more protein in tofu processing wastewater compared with the other wastewater. The results suggest potential applications of the PNSB strains for efficient conversions of organic compounds in wastes into biomass of high nutritional values.